2019
DOI: 10.1093/ajcn/nqz234
|View full text |Cite
|
Sign up to set email alerts
|

EPA and DHA have divergent effects on serum triglycerides and lipogenesis, but similar effects on lipoprotein lipase activity: a randomized controlled trial

Abstract: Background Comparative studies suggest that DHA may have stronger serum triglyceride–lowering effects than EPA; however, the molecular basis for this differential effect remains unexplored in humans. Differential regulation of lipogenesis and triglyceride clearance are 2 possible mechanisms of action. Objectives We compared the effects of EPA and DHA supplementation on serum triglycerides, markers of lipogenesis, and lipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 30 publications
1
36
0
1
Order By: Relevance
“…Fatty acid synthase expression itself is similarly upregulated in aromatase‐KO mice that cannot synthesize estrogen (Hewitt et al, 2004) and further highlights the transcriptional role for estrogen and lipogenesis. Although we previously demonstrated that EPA supplementation for 12 weeks increases de novo lipogenesis (Klingel et al, 2019), there were no sex effects of EPA supplementation on the change in δ 13 C of any SFA or MUFA measured, but DHA supplementation did result in a larger decrease in the percentage of plasma 18:1n‐9 in males. Conversely, lower consumption of added sugars by females could also explain the lower δ 13 C‐16:0, 16:1n‐7, and 18:0 in females; however, diet records were not collected.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Fatty acid synthase expression itself is similarly upregulated in aromatase‐KO mice that cannot synthesize estrogen (Hewitt et al, 2004) and further highlights the transcriptional role for estrogen and lipogenesis. Although we previously demonstrated that EPA supplementation for 12 weeks increases de novo lipogenesis (Klingel et al, 2019), there were no sex effects of EPA supplementation on the change in δ 13 C of any SFA or MUFA measured, but DHA supplementation did result in a larger decrease in the percentage of plasma 18:1n‐9 in males. Conversely, lower consumption of added sugars by females could also explain the lower δ 13 C‐16:0, 16:1n‐7, and 18:0 in females; however, diet records were not collected.…”
Section: Discussionmentioning
confidence: 61%
“…Despite generally higher levels of plasma 16:0, 18:0, and 18:1n‐9 in females at baseline, we found lower δ 13 C of 16:0, 16:1n‐7, and 18:0 in females compared with males. Variations in δ 13 C‐16:0 has been used as a marker for de novo lipogenesis (Klingel et al, 2019), and a higher δ 13 C content—likely derived from added sugars—suggests that de novo lipogenesis is a larger contributor to plasma 16:0 levels in males compared with females. Higher de novo lipogenesis has been reported in males compared with females (Pramfalk et al, 2015; Tran et al, 2010), and estrogen is thought to play a role in attenuating de novo lipogenesis in rodents (Diamant et al, 1975; Hewitt et al, 2004; Paquette et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, major limitations in the field of EPA biology need to be addressed. Notably, most preventative studies use levels of EPA that are not achievable in humans; moreover, investigators routinely rely on impure fish oil mixtures of EPA/DHA despite strong evidence that these two fatty acids are structurally and functionally distinct 25,26 .…”
Section: Introductionmentioning
confidence: 99%